Post-fire grass seeding for rehabilitation and erosion control: implications for native plant recovery and exotic species establishment - Hunter, Molly E., author; Omi, Phil, advisor; Stohlgren, Thomas J., committee member; Romme, W. H., committee member; Lauenroth, W. K., committee member (Colorado State University. Libraries, 2004)
Ponderosa pine forests of the southwestern United States are poorly adapted to the high severity wildfires. Such fires result in high mortality of understory species and increase the potential for harmful runoff and soil erosion. To mitigate the risks imposed by high severity wildfire, such areas are often aerially seeded with exotic grasses or cultivars of native grasses in hopes of rapidly establishing vegetation. Despite the wide use of these treatments their ecological effects are not well understood. The purpose of my dissertation is to determine the effects of post-fire grass seeding with exotic grasses and native cultivars (seeded grasses) on native plant recovery and exotic species establishment at the Cerro Grande wildfire in Northern New Mexico. I hypothesize that seeded grasses will dominate over native grasses due to their ability to utilize available resources and their high propagule supply. I also hypothesize that seeded grasses will facilitate establishment of exotic species through contamination of the seed mix with exotic species. Seeded grasses were found to have much higher seed density than native grasses in the seed bank in areas where they were seeded. This corresponded to higher density of seeded grasses in the above ground vegetation in the same areas. Thus high cover of seeded grasses is likely to be partly due to high propagule pressure. Dominance of seeded grasses over native grasses may also be a function of their higher growth rates in response to availability of nitrogen, as seen in a greenhouse study. This may explain why cover of seeded grasses increased up to four years after the fire in areas where nitrogen availability was high. Seeded grasses did not persist throughout the burned landscape four years after the fire. However, in areas where seeded grasses persisted, lower native grass cover and lower native species richness was found. Even when seeded grasses do not persist on the landscape, they may still pose threats to native plants. Positive correlations were found between seeded grasses and exotic species, perhaps because the seed mixes used in the erosion control treatments were contaminated with seeds of other exotic species. All these results were consistent with my original hypotheses.
Keywords: forestry; ecology; botany